2006
DOI: 10.1021/es0519278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bromide and Iodide Ions on the Formation and Speciation of Disinfection Byproducts during Chlorination

Abstract: Two natural waters were fortified with various levels of bromide or iodide ions (0-30 microM) and chlorinated in the laboratory to study the impact of bromide and iodide ions on the formation and speciation of disinfection byproducts. Trihalomethanes (THMs), haloacetic acids (HAAs), total organic halogen (TOX), and its halogen-specific fractions total organic chlorine (TOCl), bromine (TOBr), and iodine (TOI), were measured in this work. The molar yields of THMs and HAAs increased as the initial bromide concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
209
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(242 citation statements)
references
References 26 publications
(48 reference statements)
24
209
2
Order By: Relevance
“…This is 302 consistent with the theory that bromide is more effectively incorporated into low UV-absorbing, 303 low molecular weight and hydrophilic fractions, since more than 70% of AOM are hydrophilic 304 (Choi et al, 2004;Henderson et al, 2008). With regard to total DBP yield (THM and HAA), 305 however, no significant change was evident in algae samples with a bromide spike compared to 306 those without bromide; this was also reported by an earlier study of chlorination tests carried out on 307 raw water under different bromide levels (Hua et al, 2006). 308…”
Section: Haa Speciation From Cells and Eom 261mentioning
confidence: 56%
“…This is 302 consistent with the theory that bromide is more effectively incorporated into low UV-absorbing, 303 low molecular weight and hydrophilic fractions, since more than 70% of AOM are hydrophilic 304 (Choi et al, 2004;Henderson et al, 2008). With regard to total DBP yield (THM and HAA), 305 however, no significant change was evident in algae samples with a bromide spike compared to 306 those without bromide; this was also reported by an earlier study of chlorination tests carried out on 307 raw water under different bromide levels (Hua et al, 2006). 308…”
Section: Haa Speciation From Cells and Eom 261mentioning
confidence: 56%
“…The effect of bromide on DBPs formation in pool water was also investigated, since studies with drinking water have shown increased DBPs levels in the presence of bromide, as well as the formation of Br-based DBPs (Chang et al, 2001;Hua et al, 2006;Hua and Reckhow, 2008). This is due to the oxidation of Br -by the HOCl, forming of hypobromous acid (HOBr) (White, 1992).…”
Section: Effect Of Bromidementioning
confidence: 99%
“…However, bromine incorporation was expected to be unaffected by UV treatment followed by the chlorination of water from seawater pools, due to the presence of high bromide levels of seawater in this study. Furthermore, previous studies with drinking water have shown increased DBP levels in the presence of bromide, as well as the formation of brominated DBPs (Chang et al, 2001;Hua et al, 2006), which is likely due to the oxidation of bromide by hypochlorous acid to form hypobromous acid (White, 1992), the latter of which reacts with the dissolved organic matter and forms brominated DBPs. A higher level of brominated DBPs has been reported by several studies for pools filled with seawater (Chowdhury et al, 2014;Manasfi et al, 2016).…”
Section: Haloacetonitriles (Hans)mentioning
confidence: 92%